Pengaruh Penerapan Kurikulum Riset Terhadap Kemampuan Literasi Informasi Peserta Didik MA Pembangunan UIN Jakarta - Rusli (STIT Muslim Asia Afrika, 2019)
World is now facing information technology era which practically may cause information as one of basic needs in daily based life activities. In any kind of education setting such as; classroom teaching and learning activities, discussion forum either with other students or teacher, accomplishing any assignment to facing various issues, a student is believed to be working with such information. Meanwhile, employing research curriculum as a local content in Madrasah is considered to be in line with 2013 curriculum which is believed to educate every student to observe, question, and analyze material being learnt. By employing the research curriculum, every student is expected to enhance and explore their scientific skill capacity which is offered by the 2013 Curriculum. It is also believed that, this curriculum may assist every student to develop their information literacy skill as aforementioned above if research may train every student to develop information literacy skill. To put it another way, in doing research, every student searches, discovers, and analyzes information being studied. Thus, every student may possess various sub skills of information literacy such as; to search, to discover, to analyze, to evaluate, and to communicate information. These skills are considered to be important to figure out issues being faced. The present study is to analyze the correlation and influence between research curriculum as a local content toward student’s literacy information skills.